The Endoscopic Management of Pain in Chronic Pancreatitis - Adam J. Goodman; Frank G. Gress (Gastroenterology Research and Practice)
Pain resulting from chronic pancreatitis is often debilitating and difficult to manage. Many approaches have been used to treat these patients, including narcotic analgesia, antidepressants, pancreatic enzymes, octreotide, denervation procedures, such as celiac plexus block, and various palliative, decompression, or drainage procedures. Many of these procedures can be performed endoscopically, while others require a more invasive, surgical approach. The effectiveness of these therapies is not only highly variable but also often controversial. This review will discuss the endoscopic options for pain management in patients with chronic pancreatitis and their utility in treating this difficult disease.